Analisis Pengaruh Kepadatan Debu dan Penggunaan APD Pekerja Pabrik Pakan Ikan Terhadap Gangguan Fungsi Paru Pada Pekerja Pabrik Pakan Ikan di Kecamatan XIII Koto Kampar - Indrawati Indrawati; Zulkarnaini Zulkarnaini; Suyanto Suyanto (Dinamika Lingkungan Indonesia, 2015)
Cases of pulmonary disorders caused by exposure to dust are found in Indonesia, avariety of factors in the onset of respiratory illness as a result of dust covering the particlesize, shape, concentration, solubility and chemical properties as well as long exposure,several factors of karakteristi workers also can also affect the state including lung, smokinghabit, the habit of wearing personal protective equipment, exercise habits, etc. (karbella2011). The purpose of this study was to determine the effect of the analysis of ambient dustlevels and use of PPE with the incidence of pulmonary function impairment. This study usesobservational study design, with a cross-sectional design that was conducted in May-July2015 in Fish Feed Plant Koto Kampar District XIII. Number of samples 32 people.Measuring instruments used are questionnaires and observation sheets. Analiais data used issimple logistic regression. The results showed that the variables associated with impairedlung function are variable dust density (p value 0.001), use of PPE (p value 0.001), thevariable counfounding; smoking (p value 0.005), and sports (p value 0.014). While mostdominant variable affecting lung function impairment in workers fish feed is variable dustdensity (p value 0.009) and use of PPE (p value 0.023). Advised on factory workers tomaintain the safety of health themselves by using personal protective mill dust densityenvironment experienced during work.